Experimental law and economics - Isaac, R. Mark; Kitchens, Carl (Research in experimental economics ;, 2022)
Experiments. Law. Economics. Those three words taken by themselves encompass vast parts of the human intellectual experience. Even when we link them together as Experimental Law and Economics, we see a large and diverse body of inquiry over the last half century. This 21st volume of Research in Experimental Economics focuses on experimental and empirical investigations into topics about both the economic effects of the law and how economic theories can explain the behavior of individuals within a legal system. The papers in this volume follow two long-standing traditions. Firstly, the tradition of experimental methodology that allows one to test the potential impacts of alternate institutional arrangements. Secondly, a subset of the papers in this volume, in addition to exploring institutional change, follow the tradition in experimental economics of replication and robustness studies. Illuminating three key areas, by summarizing mechanisms to facilitate the assembly of property rights, exploring legal procedure, and replicating classic market experiments using more recent experimental methods to understand how different market rules affect market outcomes, each of these papers contributes to one of the broader areas within experimental law and economics.